Capital Expenditure Determinants in Central Java and East Java with Economic Growth as Moderating Variable - Pancawati Hardiningsih; Indira Januarti; Maryono Maryono; Ceacilia Srimindarti (Fakultas Ekonomika dan Bisnis UNTAG Semarang, 2020)
This study aims to analyze the effect of local own revenue, balance funds and area size on capital expenditure with economic growth as a moderating factor for district / city governments in Central and East Java Provinces. The population in this study are all districts / cities in Central Java and East Java Province. This research uses census method. The secondary data used in this study is in the form of 2015-2017 APBD realization reports obtained from the Director General of Fiscal Balance of the Regional Government, while data on economic growth and area size were obtained from BPS of Central and East Java Provinces. The analysis technique uses structural equation models with Partial Least Square. The results showed that regional original income and balance funds had a significant positive effect on capital expenditure in Central and East Java. The area size has a positive and significant effect on capital expenditure for Central Java but not for East Java. Economic growth moderates the effect of regional income on capital expenditure. Economic growth moderates balance funds towards capital expenditure for Central Java but not for East Java. Overall there is no difference in capital expenditure across districts / cities in the two provinces